2011
DOI: 10.2337/dc10-1981
|View full text |Cite
|
Sign up to set email alerts
|

Randomized Trial of a Literacy-Sensitive, Culturally Tailored Diabetes Self-Management Intervention for Low-Income Latinos

Abstract: OBJECTIVETo test whether a theory-based, literacy, and culturally tailored self-management intervention, Latinos en Control, improves glycemic control among low-income Latinos with type 2 diabetes.RESEARCH DESIGN AND METHODSA total of 252 patients recruited from community health centers were randomized to the Latinos en Control intervention or to usual care. The primarily group-based intervention consisted of 12 weekly and 8 monthly sessions and targeted knowledge, attitudes, and self-management behaviors. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

18
318
4
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 189 publications
(341 citation statements)
references
References 20 publications
18
318
4
1
Order By: Relevance
“…33,49,50,54,55 While we did find that all participants had improvements in A1C at 3 months, this improvement was not sustained at 6 months. Participants may not have maintained the skills they gained after the weekly contact ended.…”
Section: Discussioncontrasting
confidence: 57%
See 2 more Smart Citations
“…33,49,50,54,55 While we did find that all participants had improvements in A1C at 3 months, this improvement was not sustained at 6 months. Participants may not have maintained the skills they gained after the weekly contact ended.…”
Section: Discussioncontrasting
confidence: 57%
“…Previous studies testing diabetes self-management interventions have had mixed results in impacting diabetes self-care activities. 49,50 Considering that Latinos tend to struggle with lifestyle changes due to competing demands and lack of resources for lifestyle change, our study demonstrated the possibility of a church-based diabetes self-management intervention helping participants overcome their struggles in making behavior change. 12,51 Even though these outcomes are self-reported, these findings are increasingly relevant since recent studies, including LOOK AHEAD, note that improvements in diet and exercise translate to improvements in many patient-centered outcomes, such as functional status and quality of life.…”
Section: Discussionmentioning
confidence: 83%
See 1 more Smart Citation
“…Diabetes is a serious public health problem in Mexico, and the prevalence of diabetes has increased from 6.7% in 1993 to 14.42% in 2006 [1]. Approximately 95% of patients exhibit poor or very poor glycemic control due to inconsistent routine treatment [2].…”
Section: Introductionmentioning
confidence: 99%
“…However, the health service and specialized facility infrastructure requirements of patients are not clear, and it remains unclear whether this strategy is feasible for patients with little formal education, and with limited economical resources [13] [14].…”
Section: Introductionmentioning
confidence: 99%